Case report: Peri-procedural hydroxyurea helps minimize bleeding in patients with Essential Thrombocythemia associated with acquired von Willebrand syndrome - Kogan, Leah; Price, Russell; Kotchetkov, Rouslan (Frontiers in Oncology, 2024)
Background: Essential Thrombocythemia is a chronic myeloproliferative neoplasm characterized by an isolated excessive production of platelets. Extreme thrombocytosis is defined by having a platelet count greater than or equal to 1,000 x 10 9 /L, which may lead to the development of acquired von Willebrand syndrome and complications of excessive hemorrhage.Case description: A 74-year-old female patient was brought in for a bone marrow examination regarding elevated platelet count. She had no history of excessive bleeding. The physical exam was unremarkable with no petechiae or hematomas. Complete blood count showed platelet count 1,491x10 9 /L. Bone marrow aspiration and biopsy were unremarkable, however, the patient developed bleeding from the biopsy site. Local pressure and an ice pack were ineffective, so she received 20 mcg of desmopressin subcutaneously, 1 unit of fresh frozen plasma and was started on tranexamic acid 1,000 mg orally every 8 hours. She was admitted for bleeding control and had another dose of desmopressin. Blood work showed elevated partial thromboplastin time and normal international normalized ratio. Acquired von Willebrand syndrome was suspected and a sample for von Willebrand disease was sent out. The next day her bleeding continued, and her Hb decreased from 145 to 89 g/L, she became symptomatic (tachycardic) and fatigued. The coagulation profile was consistent with acquired von Willebrand syndrome. Since she continued bleeding, she received 1 unit of packed red blood cells. A high dose of hydroxyurea (3g/day) was started urgently; within 24 hours platelet count was halved, and the bleeding resolved. Blood work was repeated 24 hours later and showed normalization of partial thromboplastin time and a normal Von Willebrand profile.Patients with extreme thrombocytosis are at high risk of bleeding due to acquired Von Willebrand Syndrome. Initiation of hydroxyurea at the time of bone marrow exam helps to control platelet count and minimizes the risk of peri-procedural hemorrhage in high-risk Essential Thrombocythemia patients with suspected acquired Von Willebrand Syndrome.